SIFAT FISIKA DAN MEKANIKA KAYU JABON MERAH (Anthocephalus macrophyllus) YANG DITANAM DI WONOGIRI, 2 JAWA TENGAH - Fanny Hidayati; Sri Sunarti; Teguh Setiaji; Arif Nirsatmanto (Jurnal Hutan Tropis, 2020)
Red jabon is one of the fast growing species. It is growth well in tropical countries. It has a potential to fulfill the demand of wood. Tree imrovement program of this species has been done in Indonesia. However, information of wood properties related to tree improvement program of red jabon is limited. Therefore, wood properties such as physical and mechanical properties of this species at the progeny trial were needed to clarify. The aims of this research were to clarify the variation of physical and mechanical properties of red jabon from 5 families at5-year-old planted in Wonogiri, Central Java and relationship between air-dry density and mechanical properties. As the result, physical and mechanical properties were varied among 5 families. Based on the results, famili number 85 performed good result of physical and mechanical characteristics, eventhough the physical properties were not highest among 5 families but it was abouf the average value. Furthermore, this family showed the best values of all mechanichal characteristics tested. In addition, air-dry density has highly positive significantcorrelation with mechanical properties (static bending strength and compressive strength parallel to grain), suggesting that mechanical properties can be predicted by air-dried density.